If Your Patients Were Too Embarrassed to Go Out in Public, What Would You Do? – Public Education to Break the Stigma on Parkinson’s Disease Using Integrated Media - Jagota, Priya; Jongsuntisuk, Porntip; Plengsri, Rachaneewan; Chokpatcharavate, Marisa; Phokaewvarangkul, Onanong; Chirapravati, Vittratorn; Panyakaew, Pattamon; Sringean, Jirada; Bhidayasiri, Roongroj (Patient related outcome measures, 2020)
People with Parkinson's (PwP) often feel stigmatized, especially when their symptoms are visually prominent. In some countries, public awareness of Parkinson's disease can be minimal, leading to social challenges for PwP. A public educational campaign using videos (VDO) showing 5 PwP in different social situations that their symptoms could be a source of inconvenience to others were launched on Facebook (FB) and television (TV). We describe the process and report the impact of the campaign on patients and the public. Number of shares and likes and the first 100 comments on FB were analyzed. There were almost 1 million views, 680,000 likes, and 256,000 shares in the Center's and popular Facebook Pages within 24 hours, subsequently reaching 4.4 million views, 138,000 likes, and 78,000 shares. Patients reported changed behavior and demeanor by the public towards them. The public's comments ranged from stating that they have seen PwP without knowing what it was to requests for more information about PD to thanks for the informative VDO. People also shared their experiences with PwP. The campaign was impactful in creating awareness about PD. Creating appealing content with appropriate video length and collaborating with community groups that have relevant skills can help in creating and disseminating an educational video which creates a significant impact on society as a whole. This can be emulated to educate the public about other diseases.